2023
DOI: 10.1111/andr.13430
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions of PDE5 inhibitors: An analysis of the World Health Organization pharmacovigilance database

Abstract: BackgroundDespite their efficacy and general safety, rare but devastating adverse drug reactions have been associated with phosphodiesterase type 5 inhibitors.ObjectivesTo determine the safety profile of oral phosphodiesterase type 5 inhibitors with a particular focus on priapism and malignant melanoma.Materials and methodsIn this case–non‐case study, we queried the individual case safety reports for phosphodiesterase type 5 inhibitors within the World Health Organization global database of individual case saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…The causes of priapism included sickle cell disease in 26 (65%), malignant hemopathy in 4 (10%), idiopathic in 4 (10%), neuroleptic drugs in 3 (7.5%), and sildenafil in 3 (7.5%) 2 . According to the World Health Organization global database of individual case safety reports (VigiBase) between 1983 and 2021, a total of 31 827 individual case safety reports were identified relating to PDE5 inhibitors for sexual dysfunction 3 . Among them, the total number of priapism events was 258 (0.8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of priapism included sickle cell disease in 26 (65%), malignant hemopathy in 4 (10%), idiopathic in 4 (10%), neuroleptic drugs in 3 (7.5%), and sildenafil in 3 (7.5%) 2 . According to the World Health Organization global database of individual case safety reports (VigiBase) between 1983 and 2021, a total of 31 827 individual case safety reports were identified relating to PDE5 inhibitors for sexual dysfunction 3 . Among them, the total number of priapism events was 258 (0.8%).…”
Section: Discussionmentioning
confidence: 99%
“…2 According to the World Health Organization global database of individual case safety reports (VigiBase) between 1983 and 2021, a total of 31 827 individual case safety reports were identified relating to PDE5 inhibitors for sexual dysfunction. 3 Among them, the total number of priapism events was 258 (0.8%). Rezaee et al found 411 cases of drug-induced priapism secondary to PDE5 inhibitors reported to the Food and Drug Administration since 1998.…”
Section: Discussionmentioning
confidence: 99%
“…2 Diagnostische Kriterien der Internationalen Kopfschmerzgesellschaft für einen primären Anstrengungskopfschmerz [1]. [23]. So berichten 10% aller Männer über Kopfschmerzen nach dem Gebrauch von Sildenafil [23].…”
Section: Epidemiologieunclassified
“…PDE5 inhibitors have been used for the improvement of ED. However, the use of phosphodiesterase type 5 inhibitors has many side effects, like malignant melanoma [160,161]. Food deficits brought on by a poor diet will almost definitely exacerbate chronic diseases [162].…”
Section: Perspectives and Novelity Of Current Studymentioning
confidence: 99%